The Role of Character Education in Improving the Quality of Islamic Education at Salafiyah Al-Madinatul Munawwaroh Islamic Boarding School - Hasanah, Rizki Uswatun; Syoviana, Elvi; Andre, Lesis; Syam , Fadhli (The Future of Education Journal, 2025)
This study aims to identify and describe the information literacy skills possessed by the librarian at SMA N 1 Koto Salak, Dharmasraya Regency. Information literacy is an essential skill that must be mastered by librarians, especially in supporting the learning process and assisting students and teachers in accessing, evaluating, and utilizing information accurately and responsibly. In the digital era, where information flows abundantly, librarians are expected to possess strong information literacy skills in order to play an active role as literacy facilitators within the school.The research employs a qualitative descriptive method, using data collection techniques such as interviews, observation, and documentation. This study explores five main aspects of information literacy: identifying information needs, searching for information effectively, evaluating information, using information ethically and legally, and presenting information appropriately. The findings show that the librarian has a basic understanding of information literacy. However, there are still limitations in evaluating information and making optimal use of information technology.Based on these findings, it is recommended that the school and the education office provide continuous support through regular information literacy training, improved access to technology and digital resources, and enhanced collaboration between librarians and teachers in the learning process. In doing so, the librarian’s information literacy skills can continue to develop and positively impact the quality of library services in the school.